An Analytical Exploration of Selected Hiligaynon Poems as a Pedagogical Framework for the Development of a Localized Instructional Module Aimed at Enhancing Learners’ Creative Comprehension Skills: Mga Piling Tulang Hiligaynon: Batayan sa Pagbuo ng Lokalisadong Modyul sa Paglinang ng Malikhaing Pag-unawa - Sere, Allen (International Journal of Arts, Sciences and Education, 2025)
This study aims to develop a localized module that will enhance creative reading comprehension skills among Grade 7 students of Concepcion National High School. The study focuses on translating the selected Hiligaynon poems to Filipino and analyzing the elements, including persona, meter and rhyme, figurative language, and imagery. Also, the study aimed to determine the validity level of the Filipino translations of selected poems, as well as the validity and acceptability of the developed localized module. A descriptive-developmental research design was used to assess the validity and acceptability of the developed module. A purposive sampling technique was employed in selecting the respondents. Results showed that the translations of the Hiligaynon poems had a high level of validity (mean=4.81,sd=0.39). The localized module had a validity mean score of 4.92 (sd=0.27), and an acceptability mean score of 4.92 (sd=0.28) from teachers and 4.90 (sd=0.30) from students. There was no significant difference in the perspectives of teachers and students regarding the module’s acceptability (t-value=1.072, p-value=0.298). Furthermore, the analysis of selected Hiligaynon poems revealed their rich use of figurative language and imagery, which can help widen students’ creative comprehension. Identifying the persona and analyzing meter and rhyme contributed to a deeper comprehension of the poem’s emotions and messages. There was no significant difference in the level of acceptability between teachers and students, indicating their shared positive views of the localized module. Therefore, the developed localized module is valid and acceptable as a tool for improving creative reading comprehension skills. This study is significant in the development of a valid and acceptable localized module for enhancing creative comprehension skills in reading among Grade 7 students.